Knockdown of LncRNA PANDAR by CRISPR-dCas9 Decreases Proliferation and Increases Apoptosis in Oral Squamous Cell Carcinoma - Jia, Tingting; Wang, Fengze; Qiao, Bo; Ren, Yipeng; Xing, Lejun; Zhang, Haizhong; Li, Hongbo (Frontiers in Molecular Biosciences, 2021)
Oral squamous cell carcinoma (OSCC) is the most common malignant epithelial tumor in the oral cavity. Emerging evidence has demonstrated the important function roles of long non-coding RNAs (lncRNAs) in human cancers. LncRNA promoter of CDKN1A antisense DNA damage activated RNA (PANDAR) functions as an oncogene in multiple carcinomas, whereas its function in OSCC has not been investigated yet. The aim of our study is to investigate the possible regulatory mechanism of PANDAR in OSCC. First of all, PANDAR was highly expressed in OSCC cells and loss-of-function assays mediated by CRISPR-dCas9 observed that PANDAR silencing restrained cell proliferation and promoted cell apoptosis. Then we found and confirmed the interaction between PANDAR and serine and arginine rich splicing factor 7 (SRSF7). Subsequently, serine/threonine-protein kinase pim-1 (PIM1) was proved to be regulated by PANDAR in SRSF7-dependant way. Rescue experiments validated that PANDAR modulated the proliferation and apoptosis in OSCC through PIM1. In conclusion, PANDAR bound with SRSF7 to increase PIM1 expression, hence promoting the development of OSCC. These data shed new lights into the seeking for effective diagnostic biomarkers and therapeutic targets for OSCC patients.